2016
DOI: 10.1080/10615806.2016.1188920
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotional maltreatment and looming cognitive style in the development of social anxiety symptoms in late adolescents

Abstract: These findings highlight the need to better understand the mechanisms through which emotional abuse and peer victimization impact social looming and contribute to social anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…This is because PES is stable and habitual. Once a high PES is formed, it is easier for individuals to develop a negative explanation of fuzzy information than to ruminate about the meaning of that fuzzy information (Gonzalez-Diez et al, 2017). This result is in accordance with the theory of differential activation (Teasdale, 1988).…”
Section: Discussionsupporting
confidence: 83%
“…This is because PES is stable and habitual. Once a high PES is formed, it is easier for individuals to develop a negative explanation of fuzzy information than to ruminate about the meaning of that fuzzy information (Gonzalez-Diez et al, 2017). This result is in accordance with the theory of differential activation (Teasdale, 1988).…”
Section: Discussionsupporting
confidence: 83%
“…(2016) 410 12–13 53% 9 USA MASC SEQ .16 .37 Good (11) Sentse et al. (2017) 5645 14 51% 7 Finland FNE OB/VQ .15 .19 Fair (10) González-Díez et al. (2017) 550 16–19 56% 6 Spain SAQ-A30 PRQ n/a .16 Good (11) Mulder et al.…”
Section: Resultsmentioning
confidence: 99%
“…Parents in the present study reported higher emotional self-awareness for themselves and higher awareness of their child's emotions as a result of participating in reflective practice. Previous research demonstrates outcomes for children of parents with poor emotional control or who are emotionally volatile (Strayer & Roberts, 2004;González-Díez, Orue, & Calvete, 2017;Milojevich & Haskett, 2018); thus, results of the present study suggest that in addition to the positive perceived changes in communication, reflective practice may have additional benefits for parents' emotional control and parental communication (Haverfield & Theiss, 2017;Baumrind, 1991). However, it is important to note that some parents and athletes in the present study reported no changes following their participation in reflective practice.…”
Section: Benefits and Potential Of Reflective Practicementioning
confidence: 44%